2018
DOI: 10.1111/jpg.12699
|View full text |Cite
|
Sign up to set email alerts
|

2d Basin Modelling in the Eastern Variscan Fold Belt (Czech Republic): Influence of Thrusting on Patterns of Thermal Maturation

Abstract: This study evaluates the geothermal history of Palaeozoic sedimentary rocks from the easternmost part of the Variscan external zone in the NE Czech Republic. The objective was to investigate the geothermal history of pre‐Variscan Palaeozoic carbonates in the study area, and to assess its relationship with that of the overlying Variscan flysch. In the study area, the Palaeozoic succession occurs at the surface or is overlain by Miocene sediments of the Carpathian Foredeep. Palaeozoic nappes and the main Varisca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The boundary conditions such as paleo‐water depth (PWD), sediment–water interface temperature (SWIT), and basal heat flow (HF) must be defined throughout the simulated geologic history. The HF is the most important boundary condition and allows the maturity of potential source rocks to be predicted (Jirman, Geršlová, Kalvoda, & Melichar, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The boundary conditions such as paleo‐water depth (PWD), sediment–water interface temperature (SWIT), and basal heat flow (HF) must be defined throughout the simulated geologic history. The HF is the most important boundary condition and allows the maturity of potential source rocks to be predicted (Jirman, Geršlová, Kalvoda, & Melichar, ).…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al (, 2007), and they summarized PWD parameters of various sedimentary facies and concluded the changes of PWD within 0 to 30 m in the western Chepaizi Uplift because of the long‐term paleo‐high (Table ). User‐defined lithological compositions (Table ) assigned to individual layers were based on descriptions of drill cuttings and cores from wells P70 and Su2 (Jirman et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Time-temperature histories were reconstructed using the HeFTy 1.8.3 software package (Ketcham, 2005) applying the kinetic zircon properties of Guenther et al (2013). For samples with reset zircons the only constraint used was a minimum temperature above 200 • C between deposition and the calculated ZHe age.…”
Section: Thermochronometrymentioning
confidence: 99%
“…Lo cal and re gional un con formi ties within the Mio cene succes sion are de vel oped due to the vary ing in ten sity and ori en tation of flex ural load ing and dif fer ent in her ited geo log i cal and tectonic base ment struc ture, as well as due to the polyphase nature of the ac tive ba sin mar gin and a grad ual change in its po sition (Brzobohatý and Cicha, 1993;Eliáš and Pálenský, 1998;Nehyba and Petrová, 2000;Krzywiec, 2001;Kováè et al, 2003Kováè et al, , 2004Oszczypko et al, 2006;Nehyba and Šikula, 2007;Francírek and Nehyba, 2016). Seis mic and bore hole data show that the bed rock in the area stud ied con sists of Pro tero zoic crys tal line rocks of Brunovistulicum, De vo nian to Lower Car bon if er ous car bon ates, and Car bon if er ous siliciclastic de pos its -"Culm fa cies" of the Moravian-Silesian Pa leo zoic (Jirman et al, 2018). Ero sional rel ics of Ju ras sic and autochthonous Paleogene strata are also pres ent, es pe cially in the south ern seg ment of the area analysed (Fig.…”
Section: Geological Settingmentioning
confidence: 98%